Operative versus non-operative treatment for closed, displaced, intra-articular fractures of the calcaneus: randomised controlled trial. (24th July 2014) - Griffin, Damian; Parsons, Nick; Shaw, Ewart; Kulikov, Yuri; Hutchinson, Charles; Thorogood, Margaret; Lamb, Sarah E
Abstract : Objective To investigate whether surgery by open reduction and internal fixation provides benefit compared with non-operative treatment for displaced, intra-articular calcaneal fractures. Design Pragmatic, multicentre, two arm, parallel group, assessor blinded randomised controlled trial (UK Heel Fracture Trial). Setting 22 tertiary referral hospitals, United Kingdom. Participants 151 patients with acute displaced intra-articular calcaneal fractures randomly allocated to operative (n=73) or non-operative (n=78) treatment. Main outcome measures The primary outcome measure was patient reported Kerr-Atkins score for pain and function (scale 0-100, 100 being the best possible score) at two years after injury. Secondary outcomes were complications; hindfoot pain and function (American Orthopaedic Foot and Ankle Society score); general health (SF-36); quality of life (EQ-5D); clinical examination; walking speed; and gait symmetry. Analysis was by intention to treat. Results 95% follow-up was achieved for the primary outcome (69 in operative group and 74 in non-operative group), and a complete set of secondary outcomes were available for 75% of participants. There was no significant difference in the primary outcome (mean Kerr-Atkins score 69.8 in operative group v 65.7 in non-operative group; adjusted 95% confidence interval of difference −7.1 to 7.0) or in any of the secondary outcomes between treatment groups. Complications and reoperations were more common in those who received operative care (estimated odds ratio 7.5, 95% confidence interval 2.0 to 41.8). Conclusions Operative treatment compared with non-operative care showed no symptomatic or functional advantage after two years in patients with typical displaced intra-articular fractures of the calcaneus, and the risk of complications was higher after surgery. Based on these findings, operative treatment by open reduction and internal fixation is not recommended for these fractures. Trial registration Current Controlled Trials ISRCTN37188541 .